1991
DOI: 10.1063/1.459917
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the singlet/triplet branching ratio in the photodissociation of ketene

Abstract: The rotational distributions of CO products from the dissociation of ketene at photolysis energies 10 cm- ' below, 56, 110,200,325,425,1107, 1435, 1720, and 2500 cm-' above the singlet threshold (30 116.2 cm-'), are measured in a supersonic free jet of ketene. The CO(v!' = 0) rotational distributions at 56, 110,200,325, and 425 cm-' are bimodal. The peaks at low J's, which are due to CO from the singlet channel, show that the product rotational distribution of CO product from ketene dissociation on the singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 20 publications
2
46
0
Order By: Relevance
“…The experimental data at 355.1 nm can be interpreted with the aid of the schematic potential energy diagram shown in Figure . By analogy to ketene photodissociation, which has been studied extensively both experimentally , and theoretically, the initially prepared, electronically excited (S 1 ) dimethylketene can undergo internal conversion to the ground singlet state, S 0 , which subsequently undergoes CC bond fission to produce ground state singlet dimethylcarbene (denoted as CH 3 CCH 3 ) plus CO with no potential energy barrier expected in excess of the bond dissociation energy.…”
Section: Results and Analysismentioning
confidence: 99%
“…The experimental data at 355.1 nm can be interpreted with the aid of the schematic potential energy diagram shown in Figure . By analogy to ketene photodissociation, which has been studied extensively both experimentally , and theoretically, the initially prepared, electronically excited (S 1 ) dimethylketene can undergo internal conversion to the ground singlet state, S 0 , which subsequently undergoes CC bond fission to produce ground state singlet dimethylcarbene (denoted as CH 3 CCH 3 ) plus CO with no potential energy barrier expected in excess of the bond dissociation energy.…”
Section: Results and Analysismentioning
confidence: 99%
“…Products from the second channel are very weakly detectable at m / e = 28 using 8.8 eV photoionization, but they are observed at 9.9 eV at m / e = 28 and also yield very strong daughter ion signals at m / e = 26. By analogy to the well-studied production of singlet methylene from ketene photodissociation, , this second channel is attributed to formation of electronically excited singlet ethylidene. The singlet and triplet ethylidene channels both contribute to all of the TOF spectra in Figure ; only the relative contributions differ.…”
mentioning
confidence: 99%
“…The near-UV photodissociation of ketene (CH 2 CO) producing both singlet and triplet methylene (CH 2 ) plus carbon monoxide (CO) has been studied extensively, both theoretically and experimentally. , By analogy, electronic excitation of methylketene might be expected to produce CH 3 CH + CO. Early kinetics studies revealed that C 2 H 4 + CO were among the primary stable products and that ethylidene is likely formed initially .…”
mentioning
confidence: 99%
“…Ketene was prepared by thermal decomposition of acetic anhydride in a quartz oven at 650 o C, and purified by distilling 3 times from 196 to 77 K [10].…”
Section: Methodsmentioning
confidence: 99%
“…While a recent comparison of the corresponding features in the ultraviolet absorption spectra of both CH 2 CO and CD 2 CO suggests that the C=O stretching υ 2 mode is also a major active mode for the ns Rydberg series [7]. Most of the previous studies of the dissociation dynamics of ketene concentrated on the dissociation from 1 A 2 and 3 A 2 excited states following excitation between 300−360 nm [8][9][10][11][12]. The triplet state 3 A 2 correlates to CH 2 (X 3 B 1 )+CO(X 1 Σ + ) products with a threshold of 28250 cm −1 above the zero point energy of the ground state of ketene molecule.…”
Section: Introductionmentioning
confidence: 99%